Leading Amid Pandemic: Conceptual Framework on Ethical-Political Leadership for Crisis Management. (30th November 2022) - Yeo, Jungwon; Jeon, So Hee
Abstract: Observing frequent ethical leadership vacuums and subsequent response failures in many countries during the recent pandemic, this article aims to identify major ethical traits of political leaders during crisis management. Based on a review of relevant research in crisis management, public administration, and management studies, the authors develop a conceptual framework on ethical-political leadership for effective crisis management. The conceptual framework first presents three realms of obligations of ethical-political leaders for crisis management, including (1) obligation to the public interest, (2) obligation to authorizing processes and procedures, and (3) obligation to colleagues, then presents details of the corresponding internal goods and virtues. The article concludes with a discussion of the contribution and limitations of this research.